Zjawisko oscylacji w przyspieszonym rozwoju gospodarczym - Hellwig, Zdzisław (Wydział Prawa i Administracji UAM, 1981)
Since a long time it has been a very puzzling question for economists: how should national income be divided for consumption and accumulation to avoid economic stagnation on the one hand and introduction of too top gear into economic system on the other. Many economic models have been constructed, which should enable answering this question with the aid of various methods or more advanced mathematic tools. It is a common feature of these models that production, savings, investement processes have been considered as some sequential time functions and given in the form of statistical time series. At the same time such function has been sought (known as a strategy of national income division) for which adequate values of an integrated income would be the highest. All the attempts have been of only descriptive significance, since no practical utilization of them has been noted down in literature. In the paper the author is trying once more to answer the old question: how to divide the national income. The considerations concern optimal partition of national income for parts destined for accumulation and consumption with the aid of a mathematical model, in which a Boolean vector is used for optimization. The suggested model has such advantage that its parameters estimation is possible on generally available information of the Cential Statistical Office and it does not call for complicated mathematical calculations. It benefits by simplification of finding the optimal solution and using optimal strategy of accumulation in practice results in a significantly better issue than when stable accumulation rate is maintained. It enables at the same time — what's the most important thing — fulfilment of a strategy of accelerated economic growth with simultaneous quick raise of the population's standard of living. As a result the model enables controlling the economy in a cyclical way. It assumes introduction of accumulation, investment and consumption cycles. Its realization calls for adequate preparation to elastic controlling the economy from technical and economic specialists. From the society a great maturity is required for the acceptance of oscillations and fluctuations.
The Oscillation Phenomenon in Accelerated Economic Growth